Evolution of social networks - Tim Hellmann; Mathias Staudigl (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
Modeling the evolution of networks is central to our understanding of modern large communication systems, such as theWorld-Wide-Web, as well as economic and social networks. The research on social and economic networks is truly interdisciplinary and the number of modeling strategies and concepts is enormous. In this survey we present some modeling approaches, covering classical random graph models and game-theoretic models, which may be used to provide a unified framework to model and analyze the evolution of networks.
urn:nbn:de:0070-pub-26740274
Keywords: C73; D83; D85; 330; Soziales Netzwerk; Evolutionsökonomik; Graphentheorie; Spieltheorie; Theorie